TEKNIK SELF-REGULATED LEARNING TERHADAP PENINGKATAN KEMANDIRIAN BELAJAR - Sumanti, Dwi; Tawil, Tawil; Indiati, Indiati (Universitas Muhammadiyah Magelang, 2013)
This research aimed to verify the influence of self-regulated learning training in enhance students independence in learning. This research was use one group pre test- post test design.subject of the research choosen by purposive sampling, they are 12 students of VII B of State junior highschool 4 Magelang who had low and average independence in learning . The reseacher use independence learning scale to collect the data, to analize the data the reseacher use non parametic Wiloxon Match Pairs Test. The result showed that self-regulated learning has positif influence in enhance students independence in learning. It proof on post-test score improvement from eksperiment group. The average improvement deviation was 14%. The improvement of students independence in learning also can be found at the changed of indicator in independence learning aspect of students who got the training and not. The students felt it help to find out their own way in learning.